Bulgaria : The Dual Challenge of Transition and Accession - World Bank (Washington, DC, 2013)
The study assesses Bulgaria's progress in its transition to a market economy, and in its preparation for accession to the European Union (EU), through an analysis of economic developments during the 1990s, with special emphasis on the 1997-1999 period. It identifies the major challenges the country faces in sustaining macroeconomic stability, and accelerating growth. To maintain fiscal stability and ensure adequate public investment to gradually reduce the public debt will require building strong fiscal risk, debt management skills. The public investment required to meet the dual challenge of completing the transition, and joining the EU, is significant. The Government's remarkable reform program of the last three years, has radically transformed the economy, with conditions established for high, and sustained growth. Yet, unemployment is growing, and by and large, the standards of living have significantly declined, meaning further reforms will be needed to boost private investment, and establish the supportive institutional foundations required for a market economy. The reform agenda focuses on ensuring a public-private interface through macroeconomic stabilization, eliminating state direct interventions, and building the public-private legal framework, as well as capacity, and credibility.